A CRY–BIC negative‐feedback circuitry regulating blue light sensitivity of Arabidopsis. (9th October 2017) - Wang, Xu; Wang, Qin; Han, Yun‐Jeong; Liu, Qing; Gu, Lianfeng; Yang, Zhaohe; Su, Jun; Liu, Bobin; Zuo, Zecheng; He, Wenjin; Wang, Jian; Liu, Bin; et al.
Summary: Cryptochromes are blue light receptors that regulate various light responses in plants. Arabidopsis cryptochrome 1 (CRY1) and cryptochrome 2 (CRY2) mediate blue light inhibition of hypocotyl elongation and long‐day (LD) promotion of floral initiation. It has been reported recently that two negative regulators of Arabidopsis cryptochromes, Blue light Inhibitors of Cryptochromes 1 and 2 (BIC1 and BIC2), inhibit cryptochrome function by blocking blue light‐dependent cryptochrome dimerization. However, it remained unclear how cryptochromes regulate the BIC gene activity. Here we show that cryptochromes mediate light activation of transcription of the BIC genes, by suppressing the activity of CONSTITUTIVE PHOTOMORPHOGENIC 1 (COP1), resulting in activation of the transcription activator ELONGATED HYPOCOTYL 5 (HY5) that is associated with chromatins of the BIC promoters. These results demonstrate a CRY–BIC negative‐feedback circuitry that regulates the activity of each other. Surprisingly, phytochromes also mediate light activation of BIC transcription, suggesting a novel photoreceptor co‐action mechanism to sustain blue light sensitivity of plants under the broad spectra of solar radiation in nature. Significance Statement: BICs are negative regulators of plant blue‐light receptor cryptochrome. This study discovered a CRY‐BIC negative feedback circuitry, whereby cryptochromes mediate blue light activation of the transcription of BICs via the COP1/HY5 pathway. In addition to cryptochromes, phytochromes mediate red/far‐red light activation of BIC transcription via the same COP1/HY5 pathway. These results suggest a photoreceptor co‐action mechanism to sustain blue light sensitivity of plants under the broad spectra of solar radiation in nature.